Frictional properties of exhumed fault gouges in DFDP‐1 cores, Alpine Fault, New Zealand. Issue 2 (27th January 2014) - Boulton, Carolyn; Moore, Diane E.; Lockner, David A.; Toy, Virginia G.; Townend, John; Sutherland, Rupert
Abstract Principal slip zone gouges recovered during the Deep Fault Drilling Project (DFDP‐1), Alpine Fault, New Zealand, were deformed in triaxial friction experiments at temperatures, T, of up to 350°C, effective normal stresses, σn′, of up to 156 MPa, and velocities between 0.01 and 3 µm/s. Chlorite/white mica‐bearing DFDP‐1A blue gouge, 90.62 m sample depth, is frictionally strong (friction coefficient, μ, 0.61–0.76) across all experimental conditions tested (T = 70–350°C, σn′ = 31.2–156 MPa); it undergoes a transition from positive to negative rate dependence as T increases past 210°C. The friction coefficient of smectite‐bearing DFDP‐1B brown gouge, 128.42 m sample depth, increases from 0.49 to 0.74 with increasing temperature and pressure (T = 70–210°C, σn′ = 31.2–93.6 MPa); the positive to negative rate dependence transition occurs as T increases past 140°C. These measurements indicate that, in the absence of elevated pore fluid pressures, DFDP‐1 gouges are frictionally strong under conditions representative of the seismogenic crust.